(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2011)
In today’s world where there is so much f? learn an t,me is less, the question arises of how effective and efficient teaching can be made. Teaching is nowadays not only. limite<:f to imparting the knowledge but it has become - ,mpartmg the knowle ge in a way it can be retained by the stude?ts and pplted. There are different learning theones which are Thus, the teacher is an uncond·t· f 11oned . Nervousness, ear, sweat are uncond"t’ st1rnu1us The ringing of bell for the particular ; ioned response· conditioned stimulus as the teacher wi acher’s class i bell for her lecture rings and nervous come When the sweat on the ringing of the bell a:ss, fear and response. conditioneo 1. Unconditioned stimulus consciously or unconsciously used by the teachers. The following paper brings to light the various learning theories and how they are used in teaching.